Criterion validation of the Ladao Bent Wire Test as a measure of dexterity - Gomez, Victoria R.; Litonjua, Luis Salvador A.; Ladao, Jr., Joaquin (Adviser).
The objectives of this paper is to determine if the Ladao Bent wire test is a valid measure of dexterity by correlating its results with the Purdue Pegboard test results, to determine if the wire test is a valid tool to distinguish UP dental students from other non-manually oriented UP students and ultimately to recommend if the wire test is an appropriate screening measure for potential students in the college. 87 students from UP, 45 from the college of dentistry and 42 from the college of Social Sciences and Philosophy participated in the study. Findings show that there is a low negative correlations (-.13) between the wire test results and the pegboard test results. However, a significant difference between the dental students and the non-dental students scores in both the wire test and the pegboard test was seen (4.42 and 10.48, respectively). It can be concluded that the Ladao Bent Wire Test is a valid screening tool and its use as an admission's test is justified. But no enough evidence was found to disprove the hypothesis that it is not a valid measure of dexterity. Thus, the criterion with which it screens applicants to the college is still unknown and it is recommended that future studies center on discovering this criterion.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental schools -- Admission; University of the Philippines.College of Dentistry -- Admission; Ladao Bent Wire Test